Effect of Chloroxylenol on Gene Expression of pslA and pelA in Pseudomonas aeruginosa - Omran, Afrah Hatem; Hosain, Zaynab Adnan Abbas; Ibrahim, Hind Tahseen (Iraqi Journal of Science, 2026)
Chloroxylenol is widely used in hospitals and other healthcare facilities to reduce the growth or the microbial load of pathogens. What’s more, biofilms are a major challenge in treating P. aeruginosa infections. The genes of PslA and pelA in two operons encode two polysaccharide polymers present in the biofilm of P. aeruginosa, Psl and Pel, respectively. Therefore, the present study aimed to evaluate the contribution of chloroxylenol to the inhibition of the P. aeruginosa biofilm. Here, the intensity of biofilms was determined by the crystal violet and microtiter plate method, whereas the RT-qPCR technique was adopted to illustrate the effect of chloroxylenol on the expression of the pslA and pelA genes. The results showed that chloroxylenol suppresses the formation of biofilms and reduces the expression of both studied genes. As a result, chloroxylenol had inhibitory activity over P. aeruginosa biofilm via downregulating the pelA and pslA genes.